Knowledge, Attitude, Practice towards COVID-19 infection of nursing personnel in Nopparat Rajathanee Hospital, Thailand in 2021 - Hongpanut, Saiwaroon; Osothsinlp, Sornwit (Disease Control Journal, 2022)
An assessment of the competence of nursing personnel for responding to the COVID-19 outbreak situation is they are the main force in the care and prevention of the epidemic. This descriptive cross-sectional study was aimed to describe the knowledge, attitude, and practice towards COVID-19 infection of nursing personnel in Nopparat Rajathanee hospital, Bangkok, Thailand. The data were collected by online questionnaires and analyzed using descriptive statistics and multivariable logistic regression. A total of 554 nursing personnel were mostly female (94.9%) with a bachelor's degree or equivalent (81.4%) and worked as a registered nurse (60.3%). It was found that the sample group had a moderate level of knowledge of COVID-19 infection (62.0 ± 28.7%), the attitudes towards COVID-19 were moderate (60.8% ± 14.9%) and prevention behaviors of COVID-19 were high (91.1% ± 8.2%). For personal factors that clearly affect knowledge, including education level, and working positions as a registered nurse. However, the factor affecting the level of preventive behavior clearly was found in registered nurse 2.18 times (95% CI = 1.0 - 8.8) when compares to nurse aid. From the study it can be concluded that nursing personnel have moderate knowledge and attitudes, but they have quite good preventive behavior, especially among registered nurses. For nursing personnel other than registered nurses, knowledge and practice should be added to promote better prevention behaviors.